Assessment of antibiotic resistance patterns in Central Taiwan during the COVID-19 pandemic: A retrospective study - Yu-Wei Tseng; Chien-Wen Huang; Chih-Chieh Chen; Tze-Kiong Er (Journal of Infection and Public Health, 2024)
Background: Antimicrobial resistance (AMR) is a growing worldwide public health issue due to the overuse and inappropriate use of antibiotics. AMR has been more prevalent during the coronavirus pandemic of 2019 (COVID-19) compared to previous periods. Therefore, this study was conducted to evaluate the AMR profile of common bacteria that were isolated for routine analysis during the pandemic of COVID-19 in Central Taiwan. The main goal of this study was to examine and analyze the AMR patterns both before and after the start of the COVID-19 pandemic. Methods: We conducted a retrospective analysis of clinical samples collected from two different time periods: the 1-year period before the onset of the COVID-19 pandemic (January 2019 to December 2019) and the 2-year period following the start of the pandemic (September 2020 to September 2022). The data for this study were obtained from clinical records, and both bacterial identification and antibiotic susceptibility testing were performed using the Phoenix identification system. Results: Among the 8152 bacterial isolates obtained during the study period from September 2020 to September 2022, 4022 (49.3%) were Escherichia coli, 1346 (16.5%) were Klebsiella pneumoniae, 1156 (14.2%) were Staphylococcus aureus, 887 (10.9%) were Pseudomonas aeruginosa, 376 (4.6%) were Enterococcus faecium, and 365 (4.5%) were Acinetobacter baumannii. The overall prevalence of resistant bacteria during the COVID-19 pandemic was as follows: vancomycin-resistant Enterococcus, 69%; carbapenem-resistant A. baumannii, 65%; methicillin-resistant S. aureus, 49%; carbapenem-resistant K. pneumoniae, 29%; carbapenem-resistant P. aeruginosa, 17%; and carbapenem-resistant E. coli, 2%. Carbapenem-resistant A. baumannii, vancomycin-resistant Enterococcus, carbapenem-resistant K. pneumoniae, and carbapenem-resistant E. coli increased by 19%, 10%, 2%, and 1%, respectively. On the other hand, carbapenem-resistant P. aeruginosa and methicillin-resistant S. aureus decreased by 6%, respectively. Conclusion: This study provides a comprehensive assessment of AMR during the COVID-19 pandemic in Central Taiwan. Understanding the prevalence of AMR is crucial for preventing infection and formulating disease prevention policies. Further research is warranted to elucidate the correlation between AMR and the severity of infection in COVID-19 patients.